Narrowing the gap? The global development cooperation agenda. First Semester 2014 - Prado Lallande, Juan Pablo; Rodríguez Suárez, Pedro Manuel (Revista Española de Desarrollo y Cooperación, 2023)
During the first months of the current year the global agenda for development has been characterized by a renewed dynamism able enough to drive processes devoted to tackle structural and specific problems. However, simultaneously, the development agenda in the mentioned period of time has also unattended determinants that affect and actually decrease the chances of structuring a more coherent international system, that should be consistent with global purposes such as the MDGs, international development funding, as well as more representative and democratic global governance schemes.